(untitled) (Agroindustria, Sociedad y Ambiente, 2013)
Silage is a benefit in livestock production, supplies the nutritional requirements of a commercial supplement natural food derived from vegetable crops. The purpose of this research was to evaluate the physicochemical and functional characteristics of corn silage and sorghum silage samples of silage sorghum ( A) and maize (B ) were taken were obtained from the production unit Finca Santa Paula Municipal Urdaneta Lara State. Each physicochemical and functional analyzes were performed in triplicate . T test " studentd " ( P <0.05 ) was applied . Homogeneity of variances was determined by the Fisher test using the Excel 2010 program under Windows. Meeting in the major sorghum silage moisture values ( 78.50 ± 0.64% ), pH (4.83 ± 0.12) . Acid detergent fiber (41.95 ± 0.06 % ), neutral detergent fiber ( 72.25 ± 0.92 %) , and lignin (9.13 ± 0.47 % ) . With respect to corn silage had the highest value of the functional property of water absorption (3.60 ± 0.20), higher percentages of the chemical properties of dry matter ( 25.84 ± 0.17 % ), crude protein (9.27 ± 0.035 ), ash (8.43 ± 0.13 %) , ether extract (1.64 ± 0.15 % ) and non- fibrous carbohydrates (24.08 ± 4.70% ) . In conclusion for the content found sorghum silage can be directed to the contribution of animal feed for growth and hours instead cows corn silage for its high concentration of carbohydrates and energy input can be used in feed for dairy cattle.